2023
DOI: 10.1002/adhm.202300161
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine‐Based Therapeutics for Myocardial Ischemic/Reperfusion Injury

Abstract: Myocardial ischemic/reperfusion (IR) injury is a global cardiovascular disease with high mortality and morbidity. Therapeutic interventions for myocardial ischemia involve restoring the occluded coronary artery. However, reactive oxygen species (ROS) inevitably impair the cardiomyocytes during the ischemic and reperfusion phases. Antioxidant therapy holds great promise against myocardial IR injury. The current therapeutic methodologies for ROS scavenging depend predominantly on administering antioxidants. Neve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 149 publications
(190 reference statements)
0
6
0
Order By: Relevance
“…However, these systems are severely disrupted during I/R, which contributes to excessive ROS production and leads to the initial myocardial reperfusion injury 33 . Thus, enhancing the activity of antioxidative enzymes may be a good strategy to decrease the oxidative stress‐elicited reperfusion damage 34,35 . Our previous work showed that F 2 protected against H/R model‐evoked oxidative injury in CMECs and myocytes 21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these systems are severely disrupted during I/R, which contributes to excessive ROS production and leads to the initial myocardial reperfusion injury 33 . Thus, enhancing the activity of antioxidative enzymes may be a good strategy to decrease the oxidative stress‐elicited reperfusion damage 34,35 . Our previous work showed that F 2 protected against H/R model‐evoked oxidative injury in CMECs and myocytes 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…33 Thus, enhancing the activity of antioxidative enzymes may be a good strategy to decrease the oxidative stress-elicited reperfusion damage. 34,35 Our previous work showed that F 2 protected against H/R model-evoked oxidative injury in CMECs and myocytes. 21,22 In agreement with these results, we found that the in vivo I/R-induced oxidative injury was also significantly alleviated by F 2 pretreatment.…”
Section: Ampk Interacts With Foxo1mentioning
confidence: 99%
“…As a consequence, the heart initiates a self-healing mechanism termed ventricular remodeling, involving the formation of fibrotic scar tissue. This process gradually induces a weakening of heart muscles, resulting in a progressive decline in muscle strength that ultimately leads to congestive heart failure and death. , Thus, there is a strong incentive for drug-delivery vehicles, including polymeric nanoparticles, to more efficiently deliver cardioprotective drugs directly into the infarcted myocardium and cardiovascular system for the diagnosis, treatment and ultimate prevention of heart failure. Oxygen therapy via sustained delivery of oxygen following myocardial infarction can effectively rescue cardiac cells and restore cardiac function . Recently, Guan et al engineered an oxygen-releasing core–shell polymeric nanoparticle to address the current limitations of oxygen delivery in treating myocardial infarctions .…”
Section: Applicationsmentioning
confidence: 99%
“…However, due to the complex pathologic factors of I/R injury, traditional treatment strategies such as blood pressure control, detumescence, and dehydration are of limited effectiveness [19,20]. Recently, advanced therapies such as ischemic preconditioning, ischemic post-treatment, antioxidant, hypothermia, and stem cell therapy have emerged as potential treatments for I/R injury [21]. Ischemic preconditioning (IPC) is considered as an effective treatment strategy for central nervous system diseases.…”
Section: Current Therapeutic Strategies For Ischemia-reperfusion Injurymentioning
confidence: 99%